Answer:
Step-by-step explanation:
201.50/13 =p 201.50/13=15.50 c /u
Answer:
x > 6
Step-by-step explanation:
![x + 3 - 5 > 4 \\ \\ x - 2 > 4 \\ \\ x > 4 + 2 \\ \\ x > 6 \\](https://tex.z-dn.net/?f=x%20%2B%203%20-%205%20%3E%204%20%5C%5C%20%20%5C%5C%20x%20-%202%20%3E%204%20%5C%5C%20%20%5C%5C%20x%20%3E%204%20%2B%202%20%5C%5C%20%20%5C%5C%20x%20%3E%206%20%5C%5C%20)
Answer:
Check the explanation
Step-by-step explanation:
Kindly check the attached image below to see the step by step explanation to the question above.
Step-by-step explanation:
1. We we can split 4p into 9p - 5p, and now we have 3p² + 9p - 5p - 15 = 0. We can take out 3p from the first 2 terms and -5 from the last 2 terms. This gets us 3p (p + 3) -5 (p + 3) = 0. These two terms have (p + 3) as a common facor, so we can take that out as well, which give us (p + 3)(3p - 5) = ). Using Zero Product Property, p + 3 = 0 and 3p - 5 = 0, and when we solve each equation, we get p = -3, p= 5/3.
2. We will use the same process.
6x² + 14x - 3x - 7 = 0
2x (3x+7) - 1 (3x+7) = 0
(3x + 7)(2x - 1) = 0
3x + 7 = 0, 2x - 1 = 0
x = -7/3, x=1/2
Hope this helps!